Operation of a MEG pilot regeneration system for organic acid and alkalinity removal during MDEA to FFCI switchover - Soames, A.; Odeigah, E.; Al Helal, A.; Zaboon, S.; Iglauer, Stefan; Barifcani, Ahmed; Gubner, Rolf (Elsevier, 2018)
© 2018 Elsevier B.V. The switch over from pH stabilisation using MDEA to film forming corrosion inhibitors (FFCI) may be beneficial following formation water breakthrough during hydrocarbon transportation and processing to prevent scaling at elevated pH and to extend the operational lifespan of a field. Where formation water is present, organic acids including acetic can be expected within MEG regeneration systems and can impose a corrosion risk together with carbon dioxide. A case study was performed to evaluate the potential of simultaneous removal of organic acids and MDEA/alkalinity during the switch over from pH stabilisation to film forming corrosion inhibitors (FFCI). Experimental testing was conducted using a MEG pilot regeneration plant operated by the Curtin Corrosion Engineering Industry Centre. Sufficient removal of organic acids was achieved to prevent accumulation within the MEG regeneration loop and subsequent corrosion issues through distillation by lowering the pH of the rich glycol feed to six to promote removal of organic acids with the water distillate. Simultaneously, removal of MDEA and reduction of lean glycol alkalinity was achieved through the reclamation system to facilitate FFCI switchover more rapidly than a comparative industrial operational methodology.